Evaluating the status of a Ramsar wetland: A study of Parvati Arga in Gonda district, Uttar Pradesh, India - Shivam Verma; Srabani Sanyal; Prashant Kushwaha (National Geographical Journal of India, 2023)
Wetlands are one of the ecotonal ecosystems in the biosphere. They provide diverse ecosystem services and habitats to a multitude of flora and fauna and are considered hotspots of biodiversity. The globally recognized Ramsar Convention signed in 1971 provides a scientific framework for the conservation and wise use of wetlands. Parvati-Arga wetland is a pair of two oxbow lakes protected as a bird sanctuary and is also a designated Ramsar site. It lies in the Saryu par flood plains in Gonda, Uttar Pradesh. This study deals with providing a comprehensive profile of the biological diversity of this wetland, identification of major threats, and also tries to uncover the lacunas of previous studies. Relevant literature has been used in this study from diverse sources like government reports, and research papers accessed from different platforms. Observations of the authors during the field visit have also been incorporated into the study to some extent. The study finds that this wetland is biologically very rich and provides habitat to many endangered species. There are many threats to the site like contamination caused by agricultural runoff, illegal fishing, and disturbance to the ecosystem caused by the grazing animals. Certain aspects of the wetlands such as land use/cover, wetland condition index, water quality analysis, and its hydro-geomorphological profile have not been studied.